eDiliman City.com a computerized government transaction system - Fernandez, Marie June M. (2001)
"EDilimancity Dot Com: A Computerized Government Transaction System" is an implementation of the study done by Prof. Paulo G. Paje on making a design that will computerize the Real Property Tax System of a City Government. This is an MIS project that does not only implement the design but also makes the computerization online. There are two kinds of users on this project. First are the employees and second are the taxpayers. Employees include the city officials such as the Coty Mayor, City Vice Mayor, SP Members and City Treasurer. In the Office of the City Assessor, an assessor can add assessed properties to the database, while in the Office of the City Treasury; it is where tax payments inquiry are done. With this project, taxpayers need not to go to the City Hall to transact business. Instead, they can file tax forms, view information pertinent to their real property and request for forms, i.e. certifications anywhere and anytime as long as they have accounts with the City Assessor for their Real Properties and of course, an Internet access. Also, we added some useful functionality that one can usually find on an Internet site. These include frequently asked questions (FAQS), help, reminders, news and calendar of events. It is also very important that the system would provide emailing system. In this project, a user can email an employee whom he/she wants to contact maybe for some questions and information. This project uses MSSQL SERVER 7 for our database and Active Server Page (ASP) with VBScript and JavaScript for our web programming and scripting. For our Operating System, we use Windows 98 with a Personal Web Server though a higher MS OS can also be used. We also use MS Visual Interdev and MS FrontPage 2000 for designing the pages used. For our email testing support, we used an Internet Information Service. Lastly, we constructed a dummy city and called it "Ediliman City" for our implementation and testing.